Adult type CML in paediatric age group – a case series from tertiary care hospital - Tiwari, Kshama; Irfan, Sumaiya; Ahmad, Sharique; Zaidi, Noorin; Farheen, Zarina (Asian Journal of Medical Sciences, 2021)
Chronic myeloid leukaemia is a clonal disorder arising from hematopoietic stem cell, affecting all the lineage of haematopoietic stem cells. The average age of affection in chronic myeloid leukaemia is 60 to 65 years and is extremely rare in childhood comprising 3% of paediatric leukaemia. An institution-based study to reveal the statistics of paediatric chronic myeloid leukaemia patients in a tertiary health care centre of North India serving mainly an economically under privileged population belonging to minority groups.